What is the role of intra-aortic balloon counterpulsation in acute myocardial infarction presenting without shock? - Divaka Perera; Kalpa De Silva (Heart International, 2012)
Percutaneous coronary intervention (PCI) in the presence of impaired left ventricular function is associated with significant mortality and morbidity, principally the underlying coronary artery disease (CAD) subtends a large proportion of viable myocardium. The consequences of the ischaemic cascade are particularly marked in this subset of patients, whose diminished physiological reserve renders them less able to withstand the consequences of ischemia or arrhythmias occurring during a PCI procedure.